IMPROVING MEDICATION SAFETY IN PUBLIC HOSPITAL SETTINGS: DEVELOPMENT AND USABILITY TESTING OF A MOBILE APP-BASED VISUAL DRUG IDENTIFICATION TOOL FOR BEDSIDE NURSES - Mona Qufayl Sayid Albathali, Fatimah Qufayl Sayid Albathali, Eman Qufayl Sayid Albathali, Dalal Qufayl Sayid Albathali, Manal Owaynan Khalaf Aljameeli, Afrah Aodah Jadie Alsaadi, (Chelonian Research Foundation, 2022)
Medication errors represent a major patient safety issue in Public hospital settings, with up to a third resulting in harm. Visual identification of drugs by bedside nurses is a frequently cited contributing factor. This study aimed to develop and test a mobile application-based visual drug identification tool to improve nurses’ accuracy and efficiency in Public medication identification. An Android prototype app providing high-resolution images of common Public drug tablets and capsules was iteratively refined based on user-centered design principles and feedback from end-user testing with 15 Public nurses. Quantitative analysis of drug identification tasks demonstrated significantly improved accuracy rates (18-31% gains) and efficiency (35-55% time reductions) using the app compared to traditional references. In qualitative assessments, nurses reported excellent usability and high perceived utility of the app. Results provide support for implementing this innovative mobile app in Public hospital units to reduce medication selection errors and improve medication safety.